(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Porosphaera, an abundant small spherical calcisponge, well known from Cretaceous strata of Europe, was found in Middle and Upper Jurassic deposits of east-central Iran. This is the first record of Porosphaera from the Jurassic, except for a questionable occurrence of the genus from the Upper Jurassic of Canada, described by Jansa et al. (1982). The following species are new: P. regularis n. sp., P. biporata n. sp., P.? labyrinthica n. sp., and P.? asymmetrica n. sp.